Cerebellar gray matter volume changes in patients with schizophrenia: A voxel-based meta-analysis - Li, Xing; Liu, Naici; Yang, Chengmin; Zhang, Wenjing; Lui, Su (Frontiers in Psychiatry, 2022)
Background: In schizophrenia, the structural changes in cerebellum are associated with cognition and motor deficits in patients. However, the findings are inconsistent owing to the heterogeneity in sample size, MRI (magnetic resonance imaging) scanners and other factors among them. Here in this study, we conducted a meta-analysis to characterize the anatomical changes in cerebellar subfields in patients with schizophrenia. Methods: Systematic research was conducted to identify studies that compare the gray matter volume (GMV) differences in the cerebellum between patients with schizophrenia and healthy controls with a voxel-based morphometry (VBM) method. A coordinate-based meta-analysis was adopted based on Seed-based d Mapping (SDM) software, and an exploratory meta-regression analysis was conducted to associate clinical and demographic features with cerebellar changes. Results: Twenty-five studies comprising 996 schizophrenia patients and 1109 healthy controls were included in the present meta-analysis. In patients with schizophrenia, decreased GMVs was demonstrated in the left Crus II, right lobule VI, and VIII, while no increased GMV was identified. In the meta-regression analysis, the mean age and illness duration were negatively associated with the GMV in the left Crus II in patients with schizophrenia. Conclusion: The most significant structural changes in the cerebellum are mainly located in the posterior cerebellar hemisphere in patients with schizophrenia. The decreased GMVs of these regions might partly explain the cognitive deficits and motor symptoms in patients with schizophrenia.